The Role of the Performance Measurement Systems on Business Process Reengineering: An Empirical Study of Turkish Small and Medium Scaled Manufacturing Firms - Zehir, Cemal; Altindag, Erkut; Gunsel, Ayse (Walter De Gruyter Gmbh, 2008)
Today, companies have begun to adopt more flexible structures to adapt to the rapidly changing environment. From the beginning of the 1990's, companies have needed radical changes to their organizational structures, especially their process methods. Companies need more flexible and faster organizational structures to respond effectively to their customers' growing variety of needs. This new concept of process reengineering has become an appealing alternative for companies. Reengineering means rebuilding an organization and its entrenched conceptions and design. Competition is intensifying today; reengineering is a convenient method of establishing a new and active structure. Reengineering tries to specify the role of performance measurement in the reengineering process. The effects of a current performance measurement system, the role of performance measurement, empowerment, integration and long-term strategic alignment are the basic subjects of reengineering. These elements are presented in this paper with positive statistical results. The results of the research and the trends observed are discussed and suggestions are presented for both managers and academicians.